Utilization Alkaline Water as An Alternative Complementary Therapy on Triglyceride Levels among Patients with Grade I Hypertension - Putri Wulandari; Ari Suwondo; Rr. Sri Endang Puji Astuti (Alta Dharma Publisher, 2020)
Cardiovascular disease a non-communicable disease with a high incidence in Indonesia. Non-communicable diseases are increasing every year, especially in Indonesia. An alternative treatment for hypertension with complementary therapy is alkaline water, which can improve triglyceride levels. This study aimed to examine alkaline water's effect as an alternative, complementary medicine on triglyceride levels among patients with hypertension grade I. This research quasi-experimental with a design using pre-test-test and post-test control group design. Data collection involved 40 respondents of phase I hypertension patients, selected through non-probability sampling with a purposive sampling method divided into two groups. The intervention group received therapy, captopril drug, and simvastatin, with the consumption of alkaline water 8.5 doses 1.5 liters per day for 21 days. In contrast, the control group was only assigned medication according to the doctor's prescription and mineral water consumption with normal power of hydrogen (pH). Independent t-test results showed significant differences with the average triglyceride levels p-value 0.000 (<0.05). The intervention group is better at lowering triglyceride levels than the control group seen from the higher difference values. Conclusion in utilizing alkaline water with a pH of 8.5 doses 1.5 liters per day for 21 days effectively reduces triglyceride levels in grade I hypertension patients